2016
DOI: 10.4317/medoral.20757
|View full text |Cite
|
Sign up to set email alerts
|

Dental anomalies inside the cleft region in individuals with nonsyndromic cleft lip with or without cleft palate

Abstract: BackgroundIndividuals with non syndromic cleft lip with or without cleft palate (NSCL±P) present high frequency of dental anomalies, which may represent complicating factors for dental treatment. The aim of this study was to investigate the prevalence of dental anomalies inside cleft area in a group of Brazilians with NSCL±P.Material and MethodsRetrospective analysis of 178 panoramic radiographs of patients aged from 12 to 45 years old and without history of tooth extraction or orthodontic treatment was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…There is numerous literature covering case reports on the occurrence of dental anomalies with unerupted permanent incisors, namely hyperdontia, ectopic eruption of permanent canines, odontomas, microdontia, transposition of permanent canines, hypodontia, enamel hypoplasia, predominantly/exclusively hypoplastic forms of amelogenesis imperfecta, molar‐incisor hypomineralization, dentigerous cyst, solitary bone cyst, regional odontodysplasia, talon cusp, horizontally‐impacted mandibular permanent lateral incisor associated with double teeth and involving the mandibular primary lateral incisor and canine, and infraoccluded primary molars . Additionally, research studies have shown the possible association of dental anomalies with the occurrence of various kinds of dental conditions, such as ectopic maxillary canine, malocclusion, non‐syndromic cleft lip with or without cleft palate, Down syndrome, hypodontia, and hyperdontia . A prospective clinical trial conducted in Malta revealed a significant association between unerupted incisors and other inheritable tooth abnormalities, such as enamel hypoplasia, hyperdontia, and ectopic teeth .…”
Section: Introductionmentioning
confidence: 99%
“…There is numerous literature covering case reports on the occurrence of dental anomalies with unerupted permanent incisors, namely hyperdontia, ectopic eruption of permanent canines, odontomas, microdontia, transposition of permanent canines, hypodontia, enamel hypoplasia, predominantly/exclusively hypoplastic forms of amelogenesis imperfecta, molar‐incisor hypomineralization, dentigerous cyst, solitary bone cyst, regional odontodysplasia, talon cusp, horizontally‐impacted mandibular permanent lateral incisor associated with double teeth and involving the mandibular primary lateral incisor and canine, and infraoccluded primary molars . Additionally, research studies have shown the possible association of dental anomalies with the occurrence of various kinds of dental conditions, such as ectopic maxillary canine, malocclusion, non‐syndromic cleft lip with or without cleft palate, Down syndrome, hypodontia, and hyperdontia . A prospective clinical trial conducted in Malta revealed a significant association between unerupted incisors and other inheritable tooth abnormalities, such as enamel hypoplasia, hyperdontia, and ectopic teeth .…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, gestational diabetes, and genetic association with the IRF6, VAX1, and PAX7 genes are consistently reported [3,4]. Most CLP patients have several hearing, feeding, speaking, and dentofacial development complications, leading to a long-term impact on the patient's facial anatomy and self-esteem [5,6]. Additionally, new evidence suggests a common basis for orofacial cleft and cortical interneuronopathy, supported by cellular and molecular central nervous system (CNS) alterations in these patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…The selected studies are described in Table 1. Regarding the general occurrence of dental anomalies, that is, the number of subjects with one or more dental anomalies, considering the specific cleft types, most of the studies indicated that some alteration in dental development occurs more frequently in individuals with CLP when compared with CL and CP (Ajami et al, 2017; Howe et al, 2015; Konstantonis et al, 2017; Matern et al, 2012; Nicholls, 2016; Paranaiba et al, 2013; Sá et al, 2016; Stahl et al, 2006; Suzuki et al, 2017; Wangsrimongkol et al, 2013; Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%